2019
DOI: 10.1177/0306624x19881926
|View full text |Cite
|
Sign up to set email alerts
|

How to Improve the YLS/CMI? Exploring a Particularly Predictive Combination of Items

Abstract: Recidivism risk assessment is central to addressing criminogenic needs among youth offenders. To accomplish this, the Youth Level of Service/Case Management Inventory (YLS/CMI) is worldwide used, but it is long and has limited predictive validity for minority populations. This study presents a particularly predictive combination of seven items that overcomes these limitations. A sample of 430 Spanish youth offenders participated in this study. The YLS/CMI long version was filled out and reconvictions were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 86 publications
(111 reference statements)
0
13
1
Order By: Relevance
“…The 7-item score was calculated by subtracting the score for the strength item from the total of the risk items. Villanueva et al (2020) found that the total 7-item score was significantly related to reoffense, yielding AUC values of .83 for the overall sample of youth and .79 for youth from ethnic minorities. These seven items, which cover content from five of the eight YLS/CMI domains, were empirically determined as the items with the strongest unique relationship to recidivism among the 42 risk items and seven strength items that compose the YLS/CMI.…”
Section: The Predictive Ability Of Yls/cmi Screening Versionsmentioning
confidence: 95%
See 3 more Smart Citations
“…The 7-item score was calculated by subtracting the score for the strength item from the total of the risk items. Villanueva et al (2020) found that the total 7-item score was significantly related to reoffense, yielding AUC values of .83 for the overall sample of youth and .79 for youth from ethnic minorities. These seven items, which cover content from five of the eight YLS/CMI domains, were empirically determined as the items with the strongest unique relationship to recidivism among the 42 risk items and seven strength items that compose the YLS/CMI.…”
Section: The Predictive Ability Of Yls/cmi Screening Versionsmentioning
confidence: 95%
“…These and other factors may shape the importance of each predictor across these countries (Muncie, 2001). However, there is some evidence that the specific combination of these seven items may be less affected by cultural issues than previous screening versions (see Villanueva et al, 2020). For example, alcohol abuse (one of the YLS/CMI domains not represented in the 7-item screening strategy) is not a risk factor for recidivism among Muslim populations in Spain, as shown in the work by Villanueva et al (2019b).…”
Section: Cultural Context Of Risk In Canada Portugal and Spainmentioning
confidence: 99%
See 2 more Smart Citations
“…The judicial case could have been opened because of a complaint, or directly by the public prosecuting authority. The study period for criminal recidivism were the two years following the baseline calendar year for all youths [27][28][29][30]. The prior criminal record was measured by reference to the presence of a judicial case in the youth's judicial record.…”
Section: Recidivism and Prior Arrest Recordsmentioning
confidence: 99%